Health Education for Parents with Toddlers with Pneumonia in The Working Area of Puskesmas Haji Pemanggilan, Central Lampung Regency, Year 2023 - Dwi Rosmawati; Fitri Windari; Heni Anggraini; Tri Riwayati Ningsih (Journal of Community Service for Health, 2023)
Pneumonia is one of the infectious diseases that affects babies and young children. According to the Health Profile of Lampung Province 2022, the three districts that contributed the most cases of pneumonia in the news showed Lampung Tengah as much as 2,872 cases, Bandar Lampung 2.468 cases and Lampung East 2.388 cases. The highest number of pneumonia sufferers from 37 health centers in Central Lampung was in the Haji Pemanggilan Health Center area with a total of 444 sufferers. The purpose of this study was to provide health education to parents about pneumonia in toddlers in the working area of Puskesmas Haji Pemanggilan in Central Lampung Regency in 2023. The data analysis method chosen was a simple quantitative descriptive model (descriptive survey). The research subjects were 61 parents of toddlers with pneumonia. From the research results, it was found that there was an increase in parental knowledge by 93%. The conclusion from this research is that there is a significant increase in the knowledge of parents of toddlers to prevent recurrent pneumonia in toddlers.